Pengaruh Efek Samping Obat Anti Tuberkulosis terhadap Kepatuhan Berobat Tuberkulosis Paru di BBKPM Surakarta - Setiawan, Made Ratna Dewi; Rima, Ana; Prasetyawati, Arsita Eka (Nexus Kedokteran Komunitas, 2013)
Background: Treatment adherence is a important factor for the recovery of patients with pulmonary tuberculosis. Many factors affect treatment adherence of pulmonary TB patients, one of which is a side effect of anti tuberculosis drugs. This study aims to analyze the influence of the side effects of anti tuberculosis drugs to the tuberculosis treatment adherence in BBKPM Surakarta. Method: This study was observational analytic with cross-sectional approach. The study was conducted in June â July 2012 in BBKPM Surakarta. A total of 48 subjects were selected by purposive sampling method and pulmonary TB patients who have been selected based on inclusion and exclusion criteria. Data retrieval is done by looking at the patientâs medical records and questionnaires. Data were analyzed using Chi-Square analysis method, with SPSS 17.00 for Windows. Result: Data were analyzed with Chi-Square test with a significance level of 0,05 and freedom degrees of 1. Obtained p value of 0.044, which means there is influence of the side effects of anti-tuberculosis drugs to the tuberculosis treatment adherence in BBKPMÂ Â Â Â Â Â Â Â  Surakarta. Conclusion: It is concluded that there is influence of the side effects of anti tuberculosis drugs to the tuberculosis treatment adherence in Surakarta BBKPM. Keywords: Side effects of drugs, treatment adherence